In-silico screening of phytochemicals from Tridax procumbens. Linn against human neutrophil elastase targeting chronic obstructive pulmonary disease - Nagarajan, Sudhakar; D., Aru; Jayalakshmi K. M., Divya; Shankar Gupta, Prem; Kumar Pal, Ajay; Rani, Soniya (Trends in Immunotherapy, 2024)
With increasing environmental pollution (rising levels of air borne allergens) and smoke inhalational habits, biomass smoke, etc. all affect lung health, leading to various chronic lung diseases, and among them, life-threatening chronic obstructive pulmonary disease (COPD) is growing in prevalence around the globe. Thus, it’s a great demand from researchers to discover novel therapeutic drugs and vaccines against COPD. Human neutrophil elastase (HNE) is a major inflammatory protein that triggers inflammation in chronic airway diseases, causing airway remodeling and cytokines release. Recently, it has emerged as a significant target for drug discovery in patients with COPD. Hence, this study aimed to investigate the In-silico screening of the phytochemical medicinal plant Tridax procumbens against COPD via targeting HNE using the Schrodinger suite 2023-1. The docking score, glide score, and binding energy were calculated by the glide program using the Prime MM-GB/SA (Molecular Mechanics with Generalized Born and Surface Area Solvation) module. The best selected phytochemicals (ligands) were then screened for pharmacokinetic properties via ADMET analysis predicted using the qikProp program. Out of the library of Tridax procumbens, the phytochemicals like Apigetrin, Puerarin, Centaureidin, and Myricetin significantly bind to the catalytic site of HNE with PHE41, CYS42, SER195, GLY193, PHE192, HIS57, CYS58, PHE215, SER214, ASN61, LEU998, PRO98, TYR94, and ASP95 as residues with a glide score of the highest binding affinity (−7.707, −7.707, −7.045, and −6.871, respectively) compared to the standard drugs; Dexamethasone (−4.964), Roflumilast (−4.833), and Fluticasone (−3.968). The ADMET analysis of these four phytochemicals showed good pharmacokinetic profiles with human oral absorption, log S, molar volume, and van der waals volume, etc. Thus, In-silico findings suggest that carrying out these phytochemicals (Apigetrin, Puerarin, Centaureidin, and Myricetin) from Tridax procumbens to validate their therapeutic potential against COPD at preclinical and clinical levels.